EXPERIMENTAL AND MODELING ANALYSES OF Al- BASED NANOCOMPOSITES MANUFACTURED VIA MOLTEN-METAL AND SOLIDIFICATION PROCESSING ASSISTED BY ULTRASONIC STIRRING TECHNOLOGY - Shian Jia (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2017)
Ultrasonic Stirring Technology (UST) is used in this study to manufacture Al-based nano-composites. Ultrasonic cavitation plays an important role in refining the microstructure, dispersing the nanoparticles and breaking up clusters of nanoparticles. In this paper, 6061/A356 alloys and Al2O3/SiC nanoparticles are used as the matrix alloys and the reinforcements, respectively. The nanoparticles were inserted into the molten alloy and dispersed by ultrasonic cavitation and acoustic streaming. A previously developed multiphase Computational Fluid Dynamics (CFD) model was used to study the cavitation and the nanodispersion phenomena during ultrasonic processing of these alloys. A comparison between the mechanical properties of the as-cast 6061 and 356 alloys and nano-composites has been performed.